SOSIALISASI PENCEGAHAN TINDAK PIDANA JUDI ONLINE DIKALANGAN ANGGOTA KARANG TARUNA DESA GEDANGAN KECAMATAN GROGOL KABUPATEN SUKOHARJO DENGAN PENDEKATAN KONSEP HUKUM ADAT DALAM ORGANISASI KARANG TARUNA - Eko Ari Wibowo; Muh. Isra Bil Ali; Nendy Akbar Rozaq Rais; Tino Feri Efendi; Muqorobin; Siti Rokhmah; Veronica Kinanthi Sihutami (LPPM ITB AAS Indonesia Surakarta, 2025)
This community service activity was carried out out of concern for the social conditions among young men and women who often engage in online gambling. Then, on the way, they got an opportunity to participate in a socialization in front of the Karang Taruna Sapta Manunggal in Gedangan Village, Grogol District, Sukoharjo Regency, precisely on Sunday, February 23, 2025, around 20:00 WIB-22:00 WIB. The method in this community service was carried out using a direct socialization method which involved ITB AAS INDONESIA KKN students and was attended by members of the Karang Taruna Sapta Manunggal. The contents of this socialization included providing an understanding to the Karang Taruna Sapta Manunggal members about the general overview of online gambling, the impact of online gambling, the legal consequences of online gambling, and efforts to minimize online gambling crimes through an activity initiation in the Karang Taruna Sapta Manunggal work program. With this activity, we hope to be part of a rational effort to prevent and minimize the occurrence of online gambling crimes among teenagers. Keywords; Karang Taruna, adat recht, Criminal act, Online Gambling.